2002
DOI: 10.2214/ajr.179.4.1790939
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Involvement in Pedal Infection: MR Analysis of Frequency, Distribution, and Spread of Infection

Abstract: MR evidence of tendon infection is present in approximately half the patients who require surgery for pedal infection. Evidence of spread of the infection along tendons is seen infrequently on MR imaging. Detection of a tendon infection could influence surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Peritendinitis was also visible as described previously [5]. In contrast, in cases of tendon and/or peritendinous infection, MRI shows a variety of signals such as circular enhancement of a tendon passing through an area of cellulitis, peritendinous fluid rim, thickening of the tendon diameter and contrast enhancement of the tendon [7].…”
Section: To the Editorsupporting
confidence: 66%
“…Peritendinitis was also visible as described previously [5]. In contrast, in cases of tendon and/or peritendinous infection, MRI shows a variety of signals such as circular enhancement of a tendon passing through an area of cellulitis, peritendinous fluid rim, thickening of the tendon diameter and contrast enhancement of the tendon [7].…”
Section: To the Editorsupporting
confidence: 66%
“…Several investigators [14,23] found MRI to be clearly superior to conventional radiog- raphy and bone scintigraphy, with a sensitivity and specifi city approaching 100% [4][5][6][7][8][9]24] , although some patients with acute fractures, recent surgery and acute neuropathic arthropathy can have juxta-articular marrow signals that mimic those of osteomyelitis [11,25] . In the present study, the sensitivity and specifi city of MRI in diagnosing osteomyelitis were 100 and 63%, respectively, which is comparable to previously reported studies [6,24] .…”
Section: Discussionmentioning
confidence: 99%
“…MRI imaging criteria used for the diagnosis of osteomyelitis, abscess, cellulitis, tenosynovitis and neuropathic joint were based on those described in previous studies [4][5][6][7][8][9] . Osteomyelitis was diagnosed when focally increased bone marrow signal on FST 2 WI ( fi g. 1 a) and focally decreased marrow signal on T 1 WI with or without cortical destruction, and focal marrow enhancement on postcontrast T 1 WI was observed ( fi g. 1 , 2 ).…”
Section: Mri Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…be limited by pre-existing neuroarthropathy, in such cases, MR imaging is mainly used to assess disease extent rather than establish the diagnosis. (41) Post-contrast MR imaging is recommended for the evaluation of soft tissue disease extent. (10) Several imaging features help differentiate neuroarthropathy with superimposed infection from uncomplicated neuroarthropathy.…”
Section: Neuroarthropathy With Superimposed Infectionmentioning
confidence: 99%